Impact of the COVID-19 pandemic on imaging case volumes in King Abdullah University Hospitals (KAUH) - Gharaibeh, Maha; El-Obeid, Eyhab; Khasawneh, Ruba; Karrar, Musaab; Salman, Mohamed; Farah, Ahmad; Ahmmed, Sammah; Al-Omari, Mamoon; Elheis, Mwaffaq; Abualigah, Laith (Frontiers in Medicine, 2023)
Objective: Coronavirus impacts not only of deaths but also the economic economy It caused a decrease in the number of radiological procedures. This study compares the number of radiological procedures between 2019 and 2020. Methods: A retrospective study was conducted in King Abdullah University Hospitals(KAUH) to compare the yearly and weekly imaging case volumes based on the service location (outpatient, inpatient, and emergency department) and the imaging modalities (X-rays, interventional radiology, ultrasound, mammogram, nuclear medicine, MRI, and CT) in 2019 and 2020. The weeks were split into two phases for 2020: the pre-COVID-19 (weeks 1–10) and the post-COVID-19 (weeks 11–20). Imaging case volumes between 2019 and 2020 were analysed. To compare the mean volumes, independent-sample t tests were used. Results: The numbers of images in 2020 were reduced by 29.26% compared to those of 2019. The post-COVID-19 period had the most observable decline of 65% regarding service locations and radiological procedures. The number of nuclear medicine cases, US and Mammography in 2020 was significantly impacted by COVID-19 in 2020 compared to the Nuclear medicine case volume (P= 0.001), US(P=0.004) and Mammography (P = 0.037) in 2019. Regarding service locations, there was a significant mean difference (ER: P= 0.012, Inpatient: P = 0.002, Outpatient: P= 0.005).Moreover, there were considerable mean differences between post- and pre-COVID-19 periods among all patient service settings and radiological modalities. Conclusion: COVID-19 pandemic impact could be clearly observed based on the decline in the number of radiological imaging. The result of this study could be an initiative to establish a national strategy plan to avoid the aforementioned effect on the health care system.